English Phonological Process Applied in Instagram Feed Video - Yuniarti Zaenab Arsala; Hanisah Hanafi; Rahman Taufiqrianto Dako (Jambura Journal of English Teaching and Literature, 2022)
This study aimed to identify and describe the phonological rules applied by the students from Instagram Feed Video in pronouncing English sound. The term of phonological rule or called phonological process is refers to the theory of Schane (1973). This study focused on four types only, which were assimilation, dissimilation, deletion, and insertion. The factors that influence the phonological rule or process were discussed during the investigation. This study employed descriptive qualitative method inquiry in describing the case of phonological rule applied in Instagram feed video whether from consonant or vowel sound. The objects of this study were students from Instagram feed videos. The data were obtained from student’s pronunciations in Instagram Feed Videos. Besides Schane’s (1973) theory, this study also utilized the other experts’ ideas as well. This study was conducted at State of Gorontalo University. The research findings showed that the phenomenon of English phonological rule or process are found in four types proposed the focus of this study which are assimilation, dissimilation, deletion, and insertion with the highest number occurrence of assimilation (13). In assimilation it is highly occur on vowel sound. The dissimilation occurs at the three positions of the word; initial, medial, and final position. In deletion, they prefer to delete one of the three adjacent consonant clusters. Meanwhile in insertion, also vowels are the most inserted to break up the strings of consonant cluster. The results revealed that the students tend to make a sound change in producing English sound due to ease their pronunciation, because some of those sound does not exist in their native language sound system, therefore they change the sound with the similar sound that available in their language sound system. The result of this study offers a significant contribution in linguistics, especially in phonology and pronunciation.